Facing the Spectator - Jan Koenderink; Andrea van Doorn; Baingio Pinna; Robert Pepperell (i-Perception, 2016)
We investigated the familiar phenomenon of the uncanny feeling that represented people in frontal pose invariably appear to “face you” from wherever you stand. We deploy two different methods. The stimuli include the conventional one—a flat portrait rocking back and forth about a vertical axis—augmented with two novel variations. In one alternative, the portrait frame rotates whereas the actual portrait stays motionless and fronto-parallel; in the other, we replace the (flat!) portrait with a volumetric object. These variations yield exactly the same optical stimulation in frontal view, but become grossly different in very oblique views. We also let participants sample their momentary awareness through “gauge object” settings in static displays. From our results, we conclude that the psychogenesis of visual awareness maintains a number—at least two, but most likely more—of distinct spatial frameworks simultaneously involving “cue–scission.” Cues may be effective in one of these spatial frameworks but ineffective or functionally different in other ones.